2019
DOI: 10.4197/islec.32-2.12
|View full text |Cite
|
Sign up to set email alerts
|

Financing Afforestation in the Organization of Islamic Cooperation Countries: What Role for Islamic Economics and Finance?

Abstract: This paper looks at environmental conservation within the growing understanding of the urgent need to confront the two menaces of desertification and deforestation through afforestation schemes in the Organization of Islamic Cooperation (OIC) member countries. Deforestation is one of the main contributors to global greenhouse gas emissions, ecosystem degradation, and from there the rising cases of poverty in the developing world. Their impacts on the economy and environment of OIC member countries has been dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…The results show that Islamic financing has an important role in reducing pollution in Malaysia through green financing schemes for industry, even though industrial employment is increasing. In another study, Abdullahi (2019) found that properly implementing Islamic finance and economics can minimize environmental damage in various countries. In Bangladesh, Islamic banking has played an important role by providing beneficial financial services to support environmental improvement (T. Khan & Mohomed, 2017).…”
Section: Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that Islamic financing has an important role in reducing pollution in Malaysia through green financing schemes for industry, even though industrial employment is increasing. In another study, Abdullahi (2019) found that properly implementing Islamic finance and economics can minimize environmental damage in various countries. In Bangladesh, Islamic banking has played an important role by providing beneficial financial services to support environmental improvement (T. Khan & Mohomed, 2017).…”
Section: Hypothesismentioning
confidence: 99%
“…In addition, previous research that directly examined the effect of Islamic finance developments on renewable energy was still limited. Most of the previous research only linked the development of Islamic finance to environmental issues (Aassouli et al, 2018;Abdullahi, 2019;Campisi et al, 2018;Kassim & Abdullah, 2017;T. Khan & Mohomed, 2017;Moghul et al, 2015;Solarin, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Aassouli et al (2018) provided the roadmap for Sub-Saharan Africa (SSA) to mitigate climate change and achieve SDGs by using green sukuk as the tool to fill the financing gap for green projects. Lastly, Abdullahi (2020) recommended some Islamic finance products to be considered for policymakers in OIC countries to solve deforestation issues. The result argued that green sukuk and cash waqf could be helpful to finance the afforestation program.…”
Section: Green Economy and Its Relevancies With Islamic Economymentioning
confidence: 99%
“…Aassouli et al 31 provided the roadmap for Sub-Saharan Africa to mitigate climate change and achieve SDGs by using green sukuk as a tool for fill financing gaps for green projects. Lastly, Abdullahi 32 recommended Islamic finance products be considered by policymakers in OIC countries as solutions to deforestation issues. The result was a suggestion that green sukuk and cash waqf be used to finance afforestation programmes.…”
Section: The Green Economy and Its Relevance To Islamic Financementioning
confidence: 99%